Climate policy: choosing the right instrument to reap an additional employment dividend - Ronnie Schöb (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
Climate protection should use environmental policy instruments that raise revenues, which can be used, for instance, to cut labour taxes to alleviate unemployment in economies suffering from high and persistent unemployment. This paper elaborates the possibilities of an employment dividend of climate policies and shows the potential importance of such a second dividend for a comprehensive cost-benefit analysis of climate policy. It is argued that national attempts to reap such a double dividend may be bound to fail if resource suppliers can respond in a way that leads to a large-scale international reallocation of environmental rents. Only a internationally coordinated uniform base tax on CO2 that complements already existing emission trading systems could keep revenues from climate policy in those countries bearing the cost of fighting global warming and thus leave them with the option on a second dividend.
Keywords: Q54; H20; 330; Climate policy; double-dividend hypothesis; employment dividend; supplier responses